High-resolution 3D non-contrast-enhanced, ECG-gated, multi-step MR angiography of the lower extremities: comparison with contrast-enhanced MR angiography - Mohrs, Oliver K.; Petersen, Steffen E.; Heidt, Martin C.; Schulze, Thomas; Schmitt, Peter; Pfoser, Sabine; Kauczor, Hans-Ulrich (European radiology, 2011)
To determine the diagnostic value of non-contrast-enhanced, 3D-high-resolution, ECG-gated, multi-step MR angiography (non-ceMRA) of the lower extremities using a modified turbo-spin-echo technique in comparison to 1.0-molar contrast-enhanced MR angiography (ceMRA) in patients with suspected peripheral vascular disease (PVD).
First published online: 13 August 2010
Gesehen am 01.09.2022